Metabolic Disturbance Induced by the Embryo Contributes to the Formation of Chalky Endosperm of a Notched-Belly Rice Mutant - Tao, Yang; Mohi Ud Din, Atta; An, Lu; Chen, Hao; Li, Ganghua; Ding, Yanfeng; Liu, Zhenghui (Frontiers in Plant Science, 2022)
Grain chalkiness is a key quality trait of rice grain, whereas its underlying mechanism is still not thoroughly understood because of the the complex genetic and environmental interactions. We identified a notched-belly (NB) mutant that has a notched-line on the belly of grains. The line dissects the endosperm into two distinct parts, the upper translucent part, and bottom chalky part in vicinity of embryo. Using this mutant, our previous studies clued the negative influence of embryo on the biochemical makeup of the endosperm, suggesting the need for in depth study of embryo effect on the metabolome of developing endosperm. This study continued to use the NB mutant to evolve a novel comparison method to clarify the role of embryo in formation of chalky endosperm. Grain samples of the wild type and NB were harvested at 10, 20, and 30 days after fertilization, and then divided into subsamples of the embryo, upper endosperm and bottom endosperm. Using non-targeted metabolomics and whole-genome RNA sequencing, a nearly complete catalog of expressed metabolites and genes was generated. Results showed that the embryo impaired the storage of sucrose, amino acid, starch and storage proteins in the bottom endosperm of NB by enhancing the expression of sugar, amino acids and peptide transporters and declining the expression of starch, prolamin and glutelin synthesis related genes. Importantly, the competitive advantage of developing embryo in extracting the nutrients from endosperm, transformed the bottom endosperm into an “exhaustive source” by diverting the carbon and nitrogen metabolism from synthetic storage to secondary pathways, resulting in impaired filling of the bottom endosperm and subsequently the formation of chalky tissue. In summary, this study reveals that embryo-induced metabolic shift in the endosperm is associated with the occurrence of grain chalkiness, which is of relevance to development of high-quality rice by balancing the embryo-endosperm interaction.